Development of Mind Mapping Based Pocketbook as a Learning Media for Accounting Services - Suranto Suranto; Cheysa Cinantya Hapsari (STAI Hubbulwathan Duri, 2025)
In response to limited learning resources at SMK Negeri 6 Surakarta—primarily PowerPoint and YouTube videos—this study aimed to develop an innovative learning medium to enhance students’ understanding of Accounting Services. This research employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) to create a digital pocket book based on mind mapping techniques. Expert validations were conducted by material and media specialists, and a product trial involved 36 tenth-grade students. Material experts rated the product at 92% (very feasible), while media experts gave a 74% feasibility score. Student trials yielded a 90.83% approval rating, indicating strong acceptance and perceived usefulness. Students reported improved conceptual understanding, increased motivation, and ease of access, as the digital format allowed learning flexibility. The use of mind mapping facilitated better visualization of complex accounting concepts, supporting both independent learning and classroom engagement. Compared to traditional tools, the pocket book's integration of structured visuals and interactive elements proved more effective in stimulating student interest and retention. The mind mapping-based pocket book is a highly feasible learning medium for vocational accounting education. Its digital nature enhances accessibility and supports flexible learning environments. Future improvements could focus on offline usability and integration with interactive features.